Combination of chemical coagulation, photo-Fenton oxidation and biodegradation for the treatment of vinasse from sugar cane ethanol distillery - Rodrigues, Carmen S. D.; Neto, Ana R.; Duda, Rose M.; Oliveira, Roberto A. de [UNESP]; Boaventura, Rui A. R.; Madeira, Luis M. (Elsevier B.V., 2017)
The post-treatment of biodigested sugarcane vinasse was envisaged in the present study following three different approaches: i) coagulation/flocculation - Approach 1; ii) combination of coagulation/flocculation with photo-Fenton reaction Approach 2; iii) coagulation/flocculation followed by biological degradation and photo-Fenton reaction - Approach 3. The coagulation/flocculation per se provided a slight increase in effluent's biodegradability, a decrease in toxicity and turbidity, and provided moderate removals of total organic carbon (TOC), biochemical oxygen demand (BOD5) and chemical oxygen demand (COD). The operating costs associated with chemicals consumption are low (5.7 R$/m(3) approximate to 1.4 (SDC)/m(3)). The second and third treatment approaches allowed to reach a nontoxic effluent, improved the biodegradability and led to similar high global organics removal efficiencies. The combined treatment consisting of coagulation/flocculation plus photo-Fenton oxidation (Approach 2) revealed to be a promising solution for treating this wastewater, in order to be recirculated into the high rate anaerobic reactor. Additionally, this solution provides smaller costs (84.9 R$/m(3) approximate to 20.2 (SIC)/m(3)) associated with chemicals and energy consumption, which are however very high. Nonetheless, this cost can be reduced by about 40% if solar radiation is used in the photo-Fenton process. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Sugarcane vinasse; Biodegradability; Toxicity; Coagulation/flocculation; Photo-Fenton oxidation; Processes combination